2004
DOI: 10.4321/s1130-01082004000100010
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal hemorrhage due to metastatic choriocarcinoma with gastric and colonic involvement

Abstract: Metastatic choriocarcinoma is a rare nonseminomatous germcell tumor with a characteristic hemorrhagic tendency due to its trophoblastic origin. Gastrointestinal tube involvement is present in less than 5% of cases, and location or therapy of these lesions can be achieved by endoscopy, angiography or surgery. Despite its being a highly curable malignant disease, the ocurrence of gastrointestinal bleeding worsens prognosis. We report a case of metastatic choriocarcinoma which manifested as melaena and was diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 4 publications
(6 reference statements)
1
11
0
4
Order By: Relevance
“…Most of these complications have been described in patients with gestational tro- phoblastic disease, but testicular choriocarcinoma in males behaves similarly [10,11]. In many cases bleeding is also the first manifestation of choriocarcinoma metastatic to the gastrointestinal tract [9,12]. Bleeding secondary to metastatic involvement of the small intestine has also been described in other testicular tumors, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these complications have been described in patients with gestational tro- phoblastic disease, but testicular choriocarcinoma in males behaves similarly [10,11]. In many cases bleeding is also the first manifestation of choriocarcinoma metastatic to the gastrointestinal tract [9,12]. Bleeding secondary to metastatic involvement of the small intestine has also been described in other testicular tumors, e.g.…”
Section: Discussionmentioning
confidence: 99%
“… 3 The stomach is the most common GI location; however, several case studies have reported lesions in the small intestine and colon. 10 It is important to distinguish a primary testicular choriocarcinoma metastasizing to the GI tract from a primary gastric choriocarcinoma. 2 Some authors recommend a testicular wedge biopsy, even in cases where a palpable testicular mass or radiologic evidence cannot be found, before labeling it as a primary gastric choriocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…It can disseminate as through lymphatic via hematic; it shows a good response to chemotherapy in spite of metastasis and possesses a 5-years survival rate ranging from 70 to 80%. However, the prognosis is worse if hemorrhagic complications are present [9]. Besides these features, it has a high proliferation rate, invasiveness, vascularization and bleeding tendency as consequence of tumoral necrosis and coagulation disorders.…”
Section: Discussionmentioning
confidence: 99%